Financial Inclusion and the Promotion of Shared Responsibility Within the Household and The Family: A Case of Small Business Owners in Masaka District, Uganda - Olive Enid Nabiryo; Charles Edaku (Research Parks Publishers, 2022)
The researcher sought to establish the relationship between financial inclusion and the promotion of shared responsibility within the household and the family, a case of Small Business Owners in Masaka District, Uganda. The research adopted a mixed methods approach. A mixed methods approach advances the systematic integration of quantitative and qualitative data within a single investigation. Study respondents included women 66.7% of whom belonged to a financial savings and/or lending group and 69.5% had personally saved or set aside some money for any reason. The findings established that 71.4% of the respondents indicated that there is sharing of roles between the man and woman in the household. Chi-square results show that there are significant relationships (p-value <0.005), between financial inclusion and indicators of promoting of shared responsibility within the household and the family, these include; Joint decision making on important issues in the home (p=0.001), the type of decisions they jointly make between the wife and husband, specifically on the sale of crops (p=0.002), crops to grow or how to use land (p=0.042), and non-farm business(p=0.030); financial inclusion also has a significant relationship with the perception of respondents on whether women should participate in making and influencing community decision making (p=0.010). The R-squared value of 0.11 shows that 11% of the variations in financial inclusion can be explained by the promotion of shared responsibility within the household and the family. These results further affirm that financial inclusion can promote sharing responsibility within the household and the family and therefore create pathways to gender equality. It is also very clear that financial inclusion also has a significant relationship on the perception of individuals on whether women should participate in making and influencing community decision making. All these can be improved with an increase in financial inclusion.